Much Ado about Handwriting: Countersigning with the Other Hand in Stevenson’s The Strange Case of Dr. Jekyll and Mr. Hyde - Castricano, Jodey (Romanticism on the Net, 2006)
AbstractRobert Louis Stevenson’s The Strange Case of Dr. Jekyll and Mr. Hyde has been seen as the nineteenth century prototype of the workings of the criminal mind. Similarly, current psychoanalytic readings of the novel suggest that it serves as a precursor to Freud’s theories on the structural model of personality, and repression and that Dr. Jekyll and Mr. Hyde can provide insight into the psychology of addiction, multiple personality disorder and borderline personality disorders, as these terms have currency in the discipline of modern psychology. Indeed, Stevenson’s novel can even be seen as a precursor to the very genre of Freud’s “case” study. In fact, current readings of Dr. Jekyll and Mr. Hyde continue to focus on its case study aspects, claiming that the novel shows “the composition and operation of the criminal mind” (Thomas qtd in Rosner, Spring 29). “Much Ado About Handwriting: Countersigning with the Other Hand in The Strange Case of Dr. Jekyll and Mr. Hyde is concerned with making a Gothic case “the composition and operation of the criminal mind,” but not because the word “composition” denotes a mental constitution that merely pre-exists the text or that the text refers to or represents a substantive criminal mind; instead the word suggests that there exists a displaced link between writing, reading, interpretation, and criminality as the shadowy “place” where the “other” begins and collusion enters the scene. Taking as a premise Jacques Derrida’s contention that “it is the ear of the other that signs,” this paper is concerned with “composition,” signatures and encryption as a way of exploring how these texts pose insoluble psychic double binds regarding the determination of criminality.